2021
DOI: 10.1162/jocn_a_01649
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness in the Eyes: A Possibility of Positive Loop between Transient Pupil Constriction and Facial Attraction

Abstract: Contrary to the long-held belief of a close linkage between pupil dilation and attractiveness, we found an early and transient pupil constriction response when participants viewed an attractive face (and the effect of luminance/contrast is controlled). While human participants were making an attractiveness judgment on faces, their pupil constricted more for the more attractive (as-to-be-rated) faces. Further experiments showed that the effect of pupil constriction to attractiveness judgment extended to intrins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In addition, the positive correlation in Experiment 1 is consistent with the findings of a previous study examining the relationship between aesthetic pleasure and pupillary response 11 . Further, the negative correlation in Experiment 2 is consistent with the findings of a previous study examining the relationship between facial attractiveness and pupillary response 12 . According to the results of Experiment 1 and 2, the pictures of human faces cause the opposite pupillary response to that of other stimuli.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the positive correlation in Experiment 1 is consistent with the findings of a previous study examining the relationship between aesthetic pleasure and pupillary response 11 . Further, the negative correlation in Experiment 2 is consistent with the findings of a previous study examining the relationship between facial attractiveness and pupillary response 12 . According to the results of Experiment 1 and 2, the pictures of human faces cause the opposite pupillary response to that of other stimuli.…”
Section: Discussionsupporting
confidence: 89%
“…Aesthetic or attractiveness judgments are related to cuteness, and previous studies have shown that these judgements are correlated with changes in pupil diameter. For example, in a study which used faces as stimuli, the pupils of participants dilated as ratings of aesthetic pleasantness increased 11 and contracted as ratings of attractiveness increased 12 . Pupillary response is also associated with uncanny, which is considered to be the opposite of cute, and weaker pupillary dilation has been shown for uncanny faces 13 .…”
Section: Introductionmentioning
confidence: 99%
“…One might intuitively expect greater dilation to more attractive stimuli. To the contrary, Liao et al (2021) found that pupil diameter decreased monotonically with increasing facial attractiveness This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 90%
“…PLR is not completely reflexive; many non-visual cognitive factors, including attention (e.g., Binda et al, 2013 ; Naber et al, 2013 ), saccadic eye movement preparation ( Jainta et al, 2011 ; Mathôt et al, 2015 ; Wang et al, 2018 ; Pandey and Ray, 2021 ; Wang and Munoz, 2021 ), decision-making (e.g., de Gee et al, 2014 ; Sheng et al, 2020 ), and even subliminal stimuli can influence PLR ( Laeng et al, 2012 ; Einhäuser, 2017 ; Mathôt, 2018 ). On the other hand, pupil size too can influence cognition; for instance, movement planning ( Cherng et al, 2020 ) and esthetic appraisal evaluation ( Liao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%